2017
DOI: 10.1523/jneurosci.2810-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Epac-Phospholipase Cε Pathway Regulates Endocannabinoid Signaling and Cocaine-Induced Disinhibition of Ventral Tegmental Area Dopamine Neurons

Abstract: Exchange protein directly activated by cAMP (Epac) is a direct effector for the ubiquitous second messenger cAMP. Epac activates the phospholipase C (PLC) pathway. PLC␤ has been linked to the synthesis of the endocannabinoid 2-arachidonoylglycerol (2-AG). Here, we report that Epac facilitates endocannabinoid-mediated retrograde synaptic depression through activation of PLC. Intracellular loading of a selective Epac agonist 8-CPT-2Me-cAMP into ventral tegmental area (VTA) dopamine neurons enabled previously ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 93 publications
3
22
0
Order By: Relevance
“…4 A). Epac is a direct target for cAMP and Epac2 is highly expressed in dopaminergic neurons [45] , [46] . In the present study, we found that treatment of cells with 500 μM MPP + for 4 h decreased the expression of Epac2 to 38% compared to the control group (P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…4 A). Epac is a direct target for cAMP and Epac2 is highly expressed in dopaminergic neurons [45] , [46] . In the present study, we found that treatment of cells with 500 μM MPP + for 4 h decreased the expression of Epac2 to 38% compared to the control group (P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Midbrain slices (200 μm) from male C57BL/6J mice were prepared as described previously 39 , 40 . Mice were anaesthetized by isoflurane inhalation and decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…EPAC2 has been localized to both excitatory and inhibitory synapses (Woolfrey et al, 2009). Interestingly EPAC2 has been demonstrated to be important for excitatory transmission (Woolfrey et al, 2009; Yang et al, 2012) and has been shown to influence inhibitory transmission in dopamine neurons of the ventral tegmental area (Tong et al, 2017). Therefore, we were interested in examining whether loss of EPAC2 would impact excitatory and inhibitory synapses on the same neuron.…”
Section: Resultsmentioning
confidence: 99%